Running to Keep in the Same Place: Consumer Choice as a Game of Status - Hopkins, Ed; Kornienko, Tatiana (American Economic Review, 2004)
If individuals care about their status, defined as their rank in the distribution of consumption of one “positional” good, then the consumer's problem is strategic as her utility depends on the consumption choices of others. In the symmetric Nash equilibrium, each individual spends an inefficiently high amount on the status good. Using techniques from auction theory, we analyze the effects of exogenous changes in the distribution of income. In a richer society, almost all individuals spend more on conspicuous consumption, and individual utility is lower at each income level. In a more equal society, the poor are worse off.